'It hurts your heart': frontline healthcare worker experiences of moral injury during the COVID-19 pandemic. Issue 2 (19th December 2022) - Hegarty, Siobhan; Lamb, Danielle; Stevelink, Sharon A. M.; Bhundia, Rupa; Raine, Rosalind; Doherty, Mary Jane; Scott, Hannah R.; Marie Rafferty, Anne; Williamson, Victoria; Dorrington, Sarah; Hotopf, Matthew; Razavi, Reza; et al.
ABSTRACT: Background: Moral injury is defined as the strong emotional and cognitive reactions following events which clash with someone's moral code, values or expectations. During the COVID-19 pandemic, increased exposure to Potentially Morally Injurious Events (PMIEs) has placed healthcare workers (HCWs) at risk of moral injury. Yet little is known about the lived experience of cumulative PMIE exposure and how NHS staff respond to this. Objective: We sought to rectify this knowledge gap by qualitatively exploring the lived experiences and perspectives of clinical frontline NHS staff who responded to COVID-19. Methods: We recruited a diverse sample of 30 clinical frontline HCWs from the NHS CHECK study cohort, for single time point qualitative interviews. All participants endorsed at least one item on the 9-item Moral Injury Events Scale (MIES) [Nash et al., 2013. Psychometric evaluation of the moral injury events scale. Military Medicine, 178 (6), 646–652] at six month follow up. Interviews followed a semi-structured guide and were analysed using reflexive thematic analysis. Results: HCWs described being routinely exposed to ethical conflicts, created by exacerbations of pre-existing systemic issues including inadequate staffing and resourcing. We found that HCWs experienced a range of mental health symptoms primarily related to perceptions of institutional betrayal as well as feeling unable to fulfil their duty of care towards patients. Conclusion: These results suggest that a multi-facetted organisational strategy is warranted to prepare for PMIE exposure, promote opportunities for resolution of symptoms associated with moral injury and prevent organisational disengagement. HIGHLIGHTS Clinical frontline healthcare workers (HCWs) have been exposed to an accumulation of potentially morally injurious events (PMIEs) throughout the COVID-19 pandemic, including feeling betrayed by both government and NHS leaders as well as feeling unable to provide duty of care to patients. HCWs described the significant adverse impact of this exposure on their mental health, including increased anxiety and depression symptoms and sleep disturbance. Most HCWs interviewed believed that organisational change within the NHS was necessary to prevent excess PMIE exposure and promote resolution of moral distress.